The Influence of Social Capital on The Group Dynamics of Kebumen Ongole Crossbred (PO Kebumen) Cattle Farmers, Central Java Province, Indonesia - Sugiarto, Mochamad; Nur Cahyo, Danang (Buletin Peternakan, 2025)
This study investigates the influence of social capital comprising trust, social networks, norms, and interpersonal relationships in the group dynamics of Kebumen Ongole Crossbred (PO Kebumen) cattle farmers in Central Java, Indonesia. Utilizing a quantitative approach with an explanatory survey design, 178 respondents were selected through multi-stage random sampling. Data analysis revealed that each component of social capital significantly impacts specific dimensions of group dynamics, including group goals, organizational structure, task distribution, training and development, cohesion, work atmosphere, group pressure, effectiveness, and hidden agendas. Trust fosters cooperation and reduces conflict; social networks enhance communication and resource sharing; norms ensure group stability and alignment with shared goals; and interpersonal relationships strengthen solidarity. These findings underscore the pivotal role of social capital in enhancing group dynamics and suggest broader implications for improving the sustainability and productivity of farmer groups. Furthermore, the results highlight the potential for leveraging social capital to drive rural development and advance Indonesia's livestock industry.